ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI DENGAN MENGGUNAKAN METODE FULL COSTING DAN VARIABEL COSTING PADA TAHU MAMA KOKOM KOTABARU - Rika Sylvia (Universitas Muhammadiyah Kalimantan Timur, 2018)
Cost of production encompasses all costs and sacrifices that need to be incurred and made to produce the finished product.This study aims to analyze the calculation of cost of production Tahu Mama Kokom Kotabaru by using company method, full costing and variable costing.Based on the calculation done by using the calculation itself (company method), then the cost of production tahu per piece is Rp. 190,42, -. By using the method of full costing cost of goods sold per piece is Rp. 190,78, -. while using the method of variable costing cost of goods sold per piece is Rp. 190,62, - From the three methods known calculations applied Mama Kokom is lower than the method of full costing and variable costing.